Monitoring patients in the community with suspected Escherichia coli O157 infection during a large outbreak in Scotland in 1996. - Wood, R. (Cambridge University Press, 2001)
During outbreaks of Escherichia coli O157 a minority of patients with suspected infection develop haemolytic uraemic syndrome (HUS). The ability to identify this subgroup at an early stage is beneficial as mortality from HUS is high and may be influenced by intervention. During the 1996 Central Scotland E. coli O157 outbreak, of 886 patients from the community with suspected infection monitored at an outbreak clinic, nine developed HUS. We assessed factors associated with the development of HUS in this group. Children and the elderly were at increased risk of HUS. However, high white cell count was as least as good a predictor of HUS as age. High white cell counts predicted development of HUS with a sensitivity of 89%, specificity of 87%, positive predictive value of 7% and a negative predictive value of over 99%. We have used the results from this study along with other currently available evidence to propose a monitoring protocol for patients from the community with suspected E. coli O157 infection.